Emmerdale netissä: ohjelmakohtaisten sivustojen käyttötarkoituksen osana katselukokemusta - Tuomi, Pauliina (Tekniikan Waiheita, 2014)
Emmerdale online: The uses of a website as a part of TV watching experience In this article the role of online websites as a platform to archive and share TV-related content is analyzed trough a case study. The Finnish TV channel MTV3’s website for British TV series Emmerdale is analyzed through the linkage and purpose of the web platform to the audience. It is executed through the web platform data that covers Emmerdale’s site in 2002, 2006, 2010, 2013 and the current situation in 2014. The data is retrieved from the Internet Archives, Wayback Machine. The study examines the development of TV-related content online and the use of web platform in order to engage the audiences outside the TV broadcast. The role of social media acting as a web platform is also acknowledged to address the current situation as well as future developments.